The oral microbiota: new insight into intracranial aneurysms - Wentao Gong; Hairong Yu; Wei You; Zhen Chen; Yu Wang; Chao Liu; Youxiang Li; Sheng Guan (Annals of Medicine)
Background Intracranial aneurysms (IAs) are a significant clinical concern, with detection rates increasing due to advances in imaging technologies. However, precise mechanisms underlying their pathophysiology remain incompletely understood. Recent evidence suggests a pivotal role of oral microbiota dysbiosis, particularly periodontal pathogens, in systemic inflammation that may contribute to IA development and rupture.Objective This review aims to critically evaluate the association between oral microbiota dysbiosis and the pathogenesis of IAs, with a focus on the molecular and immunological mechanisms by which oral pathogens influence vascular pathology.Methods We conducted a comprehensive analysis of the literature regarding the impact of oral microbial dysbiosis on IA pathophysiology, emphasizing the role of specific pathogenic species, such as Porphyromonas gingivalis. The review explores how these pathogens may mediate chronic inflammation through hematogenous spread, gut microbiome alterations, and neuroinflammatory processes, leading to vascular remodeling and cerebrovascular instability.Results The findings suggest that oral microbial dysbiosis, particularly the presence of pathogenic bacteria, is implicated in the systemic inflammatory response that exacerbates the structural integrity of the cerebrovascular wall. Chronic inflammatory states induced by oral pathogens contribute to extracellular matrix degradation, impaired vascular remodeling, and an increased susceptibility to IA rupture.Conclusions The findings highlight the importance of maintaining oral microbiota homeostasis as a potential therapeutic target for preventing IAs. Interventions aimed at restoring oral microbial balance may represent a novel strategy for reducing the burden of IA formation and rupture, highlighting the need for an integrated approach to oral health and IAs prevention.